2022
DOI: 10.1371/journal.pone.0277924
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin and S&P500: Co-movements of high-order moments in the time-frequency domain

Abstract: Interactions between stock and cryptocurrency markets have experienced shifts and changes in their dynamics. In this paper, we study the connection between S&P500 and Bitcoin in higher-order moments, specifically up to the fourth conditional moment, utilizing the time-scale perspective of the wavelet coherence analysis. Using data from 19 August 2011 to 14 January 2022, the results show that the co-movement between Bitcoin and S&P500 is moment-dependent and varies across time and frequency. There is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…However, during financial instability, conditional correlations between them increase dramatically. These outcomes follow the footprint of Kumar et al (2022) and Bouri et al (2022), who found that financial stress increases the connectedness among financial assets. These dynamic results suggest that unstable cryptocurrencies may act as hedge assets for stock returns during normal times, but during economic turmoil, they are far from being hedge or safe haven instruments for the stock market.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…However, during financial instability, conditional correlations between them increase dramatically. These outcomes follow the footprint of Kumar et al (2022) and Bouri et al (2022), who found that financial stress increases the connectedness among financial assets. These dynamic results suggest that unstable cryptocurrencies may act as hedge assets for stock returns during normal times, but during economic turmoil, they are far from being hedge or safe haven instruments for the stock market.…”
Section: Resultssupporting
confidence: 78%
“…However, during financial instability, conditional correlations between them increase dramatically. These outcomes follow the footprint ofKumar et al (2022) andBouri et al (2022), who found that financial stress increases the connectednessF I G U R E 6 Wavelet coherence between US Stock Return and Cryptocurrency Return. (a) Wavelet coherence between US Stock and Bitcoin, (b) wavelet coherence between US Stock and Ethereum, (c) wavelet coherence between US Stock and Binance Coin, (d) wavelet coherence between US Stock and Dogecoin.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies tend to consider the relationship between Bitcoin prices and the aggregate US stock market index (see, among others, Bouri et al 2017a ; Baur et al 2018 ; Das et al 2020 ; Naeem et al 2020 ; Shahzad et al 2020 ; Koutmos et al 2021 ; Bouri et al 2022 ), 1 pointing to potential diversification benefits arising from the detachment of Bitcoin from the global financial system. Notably, studies examining the Bitcoin–stock nexus at the sectoral level of US stock data are few and limited.…”
Section: Introductionmentioning
confidence: 99%
“… 10 On a linked front, Kwon ( 2020 ) shows that the tail behavior of Bitcoin is associated with that of the S&P 500 index (see Kwon 2020 ). Bouri et al ( 2022 ) point to significant co-movements in the higher-order moments of the returns of Bitcoin and the S&P 500 index. …”
mentioning
confidence: 99%